English-Speaking Anxiety and Performance among Senior High School Learners - Dalit, Sherame Rose (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between English-speaking anxiety and English-speaking performance among Senior High School learners. Anchored on Foreign Language Anxiety Theory, MacIntyre and Gardner’s Processing Model of Language Anxiety, Krashen’s Affective Filter Hypothesis, and Dörnyei’s L2 Motivational Self System, the study focused on communication apprehension, fear of negative evaluation, and test anxiety as dimensions of English-speaking anxiety. A descriptive–correlational research design was used. Data were gathered from Senior High School learners using an adapted 15-item Foreign Language Classroom Anxiety Scale and learners’ English subject grades in Effective Communication. Mean, standard deviation, and Pearson product–moment correlation was used to analyze the data. Findings showed that learners experienced a very high level of English-speaking anxiety, with an overall mean of 3.35. Communication apprehension recorded the highest mean of 3.37, followed by fear of negative evaluation at 3.35 and test anxiety at 3.34. Despite this, learners showed high English-speaking performance, with a mean grade of 89.50. Correlation results revealed a significant moderate negative relationship between English-speaking anxiety and performance, r = -0.521, p = 0.023, indicating that higher anxiety is associated with lower performance. The study concludes that English-speaking anxiety is an important affective factor influencing learners’ confidence, participation, and communicative competence. It recommends supportive learning environments, learner-centered instruction, constructive feedback, language enrichment activities, and further studies on related variables and interventions. The study supports SDG 4 – Quality Education, SDG 3 – Good Health and Well-Being, SDG 8 – Decent Work and Economic Growth, and SDG 17 – Partnerships for the Goals. Its sustainability impact lies in promoting educational, institutional, socio-economic, and learner well-being sustainability through evidence-based strategies for improving English communication.